2022
DOI: 10.1126/sciadv.abm8965
|View full text |Cite
|
Sign up to set email alerts
|

Lactate induces vascular permeability via disruption of VE-cadherin in endothelial cells during sepsis

Abstract: Circulating lactate levels are a critical biomarker for sepsis and are positively correlated with sepsis-associated mortality. We investigated whether lactate plays a biological role in causing endothelial barrier dysfunction in sepsis. We showed that lactate causes vascular permeability and worsens organ dysfunction in CLP sepsis. Mechanistically, lactate induces ERK-dependent activation of calpain1/2 for VE-cadherin proteolytic cleavage, leading to the enhanced endocytosis of VE-cadherin in endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 70 publications
1
39
0
1
Order By: Relevance
“…( 35 ) unraveled that lactate production by lactate dehydrogenase A (LDHA) promotes cardiac myocyte hypertrophy. We recently observed that extracellular lactate directly impairs endothelial cell function during sepsis/septic shock and systemic administration of lactate inhibitor attenuates endothelial cell injury during sepsis ( 36 ). In the present study, we demonstrate that inhibiting lactate production markedly attenuated MI-induced cardiac dysfunction and cardiac fibrosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…( 35 ) unraveled that lactate production by lactate dehydrogenase A (LDHA) promotes cardiac myocyte hypertrophy. We recently observed that extracellular lactate directly impairs endothelial cell function during sepsis/septic shock and systemic administration of lactate inhibitor attenuates endothelial cell injury during sepsis ( 36 ). In the present study, we demonstrate that inhibiting lactate production markedly attenuated MI-induced cardiac dysfunction and cardiac fibrosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether the excessive H 2 S released by 1 -JK-PS-FA in tumor cells could regulate the vascular endothelial conditions, the expression of VE-cadherin, claudin-5, and phalloidin (three major proteins in vascular endothelial cells that regulate endothelial vascular permeability) , was first examined using a transwell system (Figure c). Immunofluorescence staining revealed substantial loss and disruption of both VE-cadherin and claudin-5 expressions in HUVECs (cultured in the lower chamber), while there was obvious upregulation of the phalloidin expression in HUVECs when HeLa cells (in the upper chamber) were incubated with 1 -JK-PS-FA (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…2‐Deoxy‐ d ‐glucose, an analog of glucose, affects the metabolism of the rate‐limiting enzyme HK and inhibits glycolysis (Wang, Zhang et al, 2022; Yang et al, 2022). Following dose–response treatment with 2‐DG in LPS‐treated RAW264.7 cells, the expression levels of NLRP3, pro‐caspase‐1 and pro‐IL‐lβ were significantly downregulated, and there was a dramatic decrease in the expression of HK1 (Figure 7 and Table S7).…”
Section: Resultsmentioning
confidence: 99%